Studies on the Processing and Preservation of Dragon Fruit (Hylocereus undatus) Jelly (The Agriculturists, 2012)
The aim of the study was to analyze the proximate composition of Dragon fruit (Hylocereus undatus) and to develop dragon fruit jelly to assess its prospect in marketability. The proximate analysis showed moisture 87.90±0.03%, ash 87.90±0.03%, reducing sugar 4.50±0.04%, non-reducing sugar 3.50±0.01%, total sugar 8.00±0.01%, total soluble solid 11±0.13%, pH 4.20±0.02%, acidity 0.45±0.01% and vitamin-C 9.90±0.04%. Then the dragon fruit jelly was prepared with standard formulation (0.05%, 0.1% and 1.5% of pectin) was analyzed for its nutritional composition with standard method. The three samples contained more or less similar nutritional compositions. The products were stored at ambient temperature (27 0C to 34 0C) for a period of 6 months and quality parameters were assessed. During storage the changes in color, flavor, odor, TSS and pH was observed. No special change of ingredients was found during first 4 months of storage and a little change of pH was observed after 4th months. A taste panel consisting of 10 panelists adjudged the acceptability of the samples. The consumer preferences were measured by statistical analysis. Among the samples jelly containing 1.5% pectin secured the highest score for color, flavor, turbidity and overall acceptability. DOI: http://dx.doi.org/10.3329/agric.v10i2.13139 The Agriculturists 2012; 10(2) 29-35